2021
DOI: 10.1016/j.tranon.2020.100889
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy: Future directions of immunotherapy in small cell lung cancer

Abstract: Small cell lung cancer (SCLC), an aggressive and devastating malignancy, is characterized by rapid growth and early metastasis. Although most patients respond to first-line chemotherapy, the majority of patients rapidly relapse and have a relatively poor prognosis. Fortunately, immunotherapy, mainly including antibodies that target the cytotoxic T lymphocyte antigen-4 (CTLA-4), checkpoints programmed death-1 (PD-1), and programmed death-ligand 1 (PD-L1) to block immune regulatory checkpoints on tumor cells, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 107 publications
1
28
0
Order By: Relevance
“… 7 ORR of PD-1 blockades monotherapy was approximately <20% regardless of PD-L1 expression. 13 The overall response of anlotinib plus PD-1 blockades in our study suggested the potentially synergistic action for cancer therapy, which was in accordance with the conclusion observed in patients with hepatocellular carcinoma who were treated with atezolizumab plus bevacizumab combination therapy. 15 Interestingly, a recent study initiated by Fan et al performed a multicenter phase II clinical trial to identify the efficacy and safety of camrelizumab (PD-1 blockade) plus apatinib (another antiangiogenic targeted drug) in ES-SCLC.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“… 7 ORR of PD-1 blockades monotherapy was approximately <20% regardless of PD-L1 expression. 13 The overall response of anlotinib plus PD-1 blockades in our study suggested the potentially synergistic action for cancer therapy, which was in accordance with the conclusion observed in patients with hepatocellular carcinoma who were treated with atezolizumab plus bevacizumab combination therapy. 15 Interestingly, a recent study initiated by Fan et al performed a multicenter phase II clinical trial to identify the efficacy and safety of camrelizumab (PD-1 blockade) plus apatinib (another antiangiogenic targeted drug) in ES-SCLC.…”
Section: Discussionsupporting
confidence: 91%
“… 12 Consequently, more effective combination treatment regarding immunotherapy was needed to prolong the survival for patients with SCLC urgently. 13 …”
Section: Introductionmentioning
confidence: 99%
“…However, the findings still need to be assessed in large samples. Nevertheless, compared with single chemotherapy, PD-L1 inhibitor with chemotherapy for SCLC patients presented beneficial OS (A et al, 2019) ( 40 ), and there is increasing evidence that shows that combination therapy, such as combined with chemotherapy, radiotherapy, and other targeted therapy, may overcome the low response to ICI among SCLC patients ( 38 , 41 , 42 ).…”
Section: Introductionmentioning
confidence: 99%
“…This leads to the release, uptake, and processing of neoantigens followed by transport to regional lymph nodes. Importantly, the radiation-induced neoantigens are only present on cancer cells [14,15]. These tumor-specific antigens allow immune targeting and cross-presentation facilitating the recognition of the radiated tumors heterogeneous mutations producing a sort of personalized "in-situ vaccine."…”
Section: Discussionmentioning
confidence: 99%
“…These tumor-specific antigens allow immune targeting and cross-presentation facilitating the recognition of the radiated tumors heterogeneous mutations producing a sort of personalized "in-situ vaccine." [3,12,14] There is the possibility that the HPV-L1 vaccine which was injected throughout the tumor to account for genetic heterogeneity may have had an effect in attracting local macrophage, NK, and dendritic cells (Figure 2). Moreover, we cannot completely exclude the contribution of the trauma from repeated "needling" of the tumor, which may have added to the inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%